Evidentiary Means in Feudal Transylvania. Ordeal by Fire (Holding a Red-hot Iron) - MOLDOVAN, Iosif Florin (Journal of Legal Studies, 2017)
One of the evidentiary means used in medieval legal procedure was the so-called judgment of God, judicium dei, also known as ordeal, from the Latin term ordalium. Ordeals were characteristic of all peoples in their various stages of development. They were based on the belief that divinity could intervene and perform miracles, disregarding the laws of nature, in order to prove one’s innocence. In the Middle Ages ordeals were widespread on the territory of Transylvania, too, the ordeal of fire being one of the most commonly used means of proof. In this paper I will try to show the characteristics of this evidence in relation to others that were used at that time, looking at them through the lenses of the documents of the time and of personal research.